Effect of Water Adsorption on Conductivity in Epitaxial Sm0.1Ce0.9O2-δ Thin Film for Micro Solid Oxide Fuel Cells Applications. (21st September 2015) - Yang, Nan; Strelcov, Evgheni; Belianinov, Alex; Tebano, Antonello; Foglietti, Vittorio; Schlueter, Christoph; Lee, Tien-Lin; Jesse, Stephen; Kalinin, Sergei V.; Balestrino, Giuseppe; Aruta, Carmela
Abstract : Water adsorption, splitting, and proton liberation were investigated on Sm0.1 Ce0.9 O2-δ thin films by scanning probe microscopy. An irreversible volume expansion was observed by applying a positive bias with increased temperature. The volume expansion is also linearly dependent on the relative humidity. A reversible water adsorption process and its effect on the conductivity were also investigated by electrochemical strain microscopy and first order reversal curve under a number of experiment conditions. The presence of a Ce 3+ along with OH groups, detected by hard x-ray photoemission spectroscopy established a clear correlation between the water incorporation and the valence state of Ce.